Icon of the Holy Apostles Peter and Paul from Belozersk and Its Place in the History of Old Russian Art of the First Third of the 13th Century - Shalina, Irina A. (Actual Problems of Theory and History of Art, 2023)
The icon of the Apostles Peter and Paul was discovered in 1926 in the iconostasis of the church of the same name in Belozersk and was received by the State Russian Museum from the Moscow Central Restoration Workshops in 1934. Judging by its precious decoration described in different sources, it was a revered urban image. Brief references invariably note the traditional character of its iconography, allegedly repeating an 11th-century work from the St. Sophia Cathedral in Novgorod. Yet, this is a unique example of the frontal depiction of two apostles with poses and gestures almost mirroring each other. It deviates from the Byzantine scheme, which often placed Paul at the right hand of Christ, but more importantly, represented the figures turned to each other in prayer to the Savior. In our opinion, such a stable composition was formed as a result of highlighting the core of the scene of the transmission of the Law or the Keys — Traditio legis or Traditio clavium. The frontal positioning of the saints, emphasized in this case, corresponded to the search in the Russian art of the 13th century for an open frontal image of a prayer and reflected the idea of the triumphant inviolability of heavenly beings, so characteristic of that epoch. The composition is based on the idea of the wholeness of a paired portrait, which has become especially widespread in Russian icon painting — a capacious image of the world order and spiritual brotherhood. Subsequently, the iconography of St. Peter and Paul standing upright is known from isolated examples, most likely repeating the famous monuments, including the one from Belozersk.The work is traditionally dated within a wide range from the end of the 12th to the middle of the 13th century, although stylistic features make it possible to attribute it to the 1220s. The same uncertainty is inherent in the historiography regarding the attribution of the painting and the identification of an artistic center. Beginning with V. Lazarev, most of the researchers, including E. Smirnova and G. Kolpakova, linked the icon with Novgorod. V. Antonova and A. Rybakov, and recently L. Lifshitz considered the work close to the Rostov-Yaroslavl circle of monuments, which seems fair. Indeed, the figurative structure does not resemble the Novgorod monuments at all: in contrast to their heroic pathos, their strict and declarative beginning, a softened and even soulful intonation prevails in it, and for all the emphasized symmetry, it is distinguished by greater spatial freedom. The artist of the work in question also avoids bright color contrasts, replacing the palette with muted warm silvery shades of bleached paints. The Central Russian nature of the artistic style is also justified by the historical status of Belozersk, which for a long served as the appanage of Rostov princes and separated in 1238 into an independent principality.
Keywords: Apostles Peter and Paul; iconography; Old Russian art; Byzantine and Russian painting of the 13th century; Belozersk; Rostov; artistic style